PUTUSAN MAJELIS KEHORMATAN MAHKAMAH KONSTITUSI TERHADAP KETUA MAHKAMAH KONSTITUSI ANWAR USMAN: Decision Of The Honour Panel Of The Constitutional Court Against The Chairman Of The Constitutional Court Anwar Usman - Ghaly Odeliatama Sinulingga; Yogo Pamungkas (Reformasi Hukum Trisakti, 2024)
The Constitutional Court was established primarily to provide judicial review. Two main questions are whether Decision No. 2/MKMK/L/11/2023 of the Constitutional Court's Honorary Council complies with Law No. 24 of 2003 and Constitutional Court Regulations No. 4 of 2012 and No. 1 of 2023, and why the judges of the Constitutional Court's Honorary Council did not dismiss the Chairman of the Constitutional Court, Anwar Usman, as a constitutional judge in that decision. This thesis employs normative research methodology that is descriptive in character. backed up by secondary information obtained from primary, secondary, and tertiary legal sources. Anwar Usman should have been dismissed dishonourably for serious ethical violations, but the judges of the Constitutional Court Honorary Council chose not to dismiss him in order to uphold the legitimacy of Decision No. 2/MKMK/L/11/2023 and prevent appeals that might jeopardize legal certainty, according to the analysis.